FOREST RESOURCE INCOME VARIATION IN MID-HILLS OF NEPAL: A CASE STUDY FROM TWO CFUGS OF PARBAT DISTRICT, NEPAL - Paudel, Ganesh (International Journal of Environment, 2015)
Inequality persists in Nepali society and various source of income including forest resource contributes to it. This study was conducted in two CFUGs of the Parbat district, Nepal and examines the variability in the forest resource income at the household level. Focus group discussion, Key informants survey and Household survey methods were employed to collect the primary data and random sample of 120 respondents were surveyed. Along with simple mathematical calculations statistical test ANOVA was performed for data analysis. Rich categories of users derive significantly more income from the CF than the middle and poor categories of users although being the larger share of CF income to the total forest income for poor users. The CF income also varies with the sex of the household head and caste of the users in absolute terms but not significant. The Gini coefficient of the income distribution is found 0.48, 0.34 and 0.31 for CF income, Private trees income and total forest income respectively. It is recommended to the CFUGs that the benefit sharing should be in the equitable basis for the sustainable use of the resources. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 1-10